Kinetic characterization of boride layers formed on AISI 316 stainless steel - Aydin, Ozlem; Topuz, Polat; Aydgomus, Tuna (CARL HANSER VERLAG, 2020)
This paper presents the growth kinetics of the boride layer formed on a boronized AISI 316 (X5CrNiMo17-12-2) stainless steel surface. Samples were boronized applying the Ekabor 2 (TM) boronizing agent in an atmosphere controlled furnace at 1073, 1173 and 1273 K for 1, 2 and 3 h by the powder pack method. Surfaces of the samples which have completed the boronizing process were prepared for metallographic examinations. An optical microscope and an integrated image analyzer were used to measure the thickness of the boride layer formed on the surface of the samples. Due to the dual phase structure of the boride layer formed on the steels in order to see these phases in detail, an SEM (Scanning Electron Microscope) image of the sample was taken with the help of the back scattered electrons. In addition, for determination of the elements constituting these phases, elemental analysis was carried out with the help of an EDS (Energy Dispersive Spectroscopy) unit connected to SEM. Then XRD (Xray diffraction analysis) analyses were carried out to understand in detail which phases formed the boron layer. For hardness measurements of boride layers, a Vickers hardness device with 100 g weight was used. Finally, to determine the growth kinetics of the boronized samples, calculations were made with the help of the Arhenius equation and compared with the literature.
Keywords: Boronizing; AISI 316; powder pack boronizing; diffusion; growth kinetics; Materials Science